Education inequality in West African countries: Does investment in education matter? - Obasuyi, Folorunso Obayemi Temitope; Chenayah, Santha; Chua, Yan Piaw (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
The paper examines whether education investment has an impact on the high quantity of education inequality in the West African (WA) countries. The paper considers inflation as a constraint to government capability to invest in education. In consequence, the study used a balanced panel data of twelve countries where education inequality is the dependent variable, and that education index serves as a proxy for education inequality since it is a measure of disparity regarding human development. The research used panel time series data from Human Development Indicators and World Bank databases, with panel data analytical techniques. The data have 16 data points that covered 1999 to 2014 with a total sample size of 192. With the presence of missing completely at random (MCAR) of the data, expectation maximisation (EM) technique was employed to replace the missing values. Although existing official data indicated that the governments of the WA countries invested 4.58% of the gross domestic product (GDP) of public expenditure that goes to education sector, which is higher than OECD countries, this research results indicate that the cumulative public expenditure that goes to education significantly increases the volume of education inequality in the WA countries. Therefore, the study concludes that amount invested seems insufficient to reduce education inequality for the countries to catch-up with the desired skill, knowledge and growth. So, the researchers propose and suggest UNESCO to have a higher rate of education expenditure as a ratio of GDP for education financing should be strictly followed in the annual government budgeting. The researchers further suggest that the region is expected to consistently develop a five-year expenditure rolling plan (ERP) on education to increase human capital stock leading to a knowledge-based economy.